Laser interstitial thermal therapy (LITT) for pediatric patients affected by intracranial tumors - Spacca, Barbara; Di Maurizio, Marco; Grandoni, Manuela; Tempesti, Sara; Genitori, Lorenzo (Frontiers in Neurology, 2023)
Introduction The surgical treatment of brain tumors has evolved over time, offering different strategies tailored to patients and their specific lesions. Among these strategies, Laser Interstitial Thermal Therapy (LITT) is one of the most recent advances in pediatric neurooncological surgery, and its results and evolution are still under assessment. Methods We retrospectively analyzed data from six pediatric patients with deep-seated brain tumors treated with LITT at a single center between November 2019 and June 2022. A total of four patients underwent a stereotaxic biopsy during the same operating session. The indications and preparation for LITT, technical issues, clinical and radiological follow-up, impact on quality of life, and oncological treatment are discussed. Results The mean patient age eight years (ranging from 2 to 11 years). The lesion was thalamic in four patients, thalamo-peduncular in one, and occipital posterior periventricular in one. In total, two patients had been previously diagnosed with low-grade glioma (LGG). Biopsies revealed LGG in two patients, ganglioglioma grade I in one, and diffuse high-grade glioma (HGG) in one. Postoperatively, two patients presented with transient motor deficits. The mean follow-up period was 17 months (ranging from 5 to 32 months). Radiological follow-up showed a progressive reduction of the tumor in patients with LGG. Conclusion Laser interstitial thermal therapy is a promising, minimally invasive treatment for deep-seated tumors in children. The results of lesion reduction appear to be relevant in LGGs and continue over time. It can be used as an alternative treatment for tumors located at sites that are difficult to access surgically or where other standard treatment options have failed.